Editorial: What makes a good article for leadership? Thoughts and views from our associate editors, part 1 - Edwards, Gareth; Schedlitzki, Doris; Carroll, Brigid; Larsson, Magnus; Jones, Owain Smolović (Leadership, 2024)
This issue of Leadership marks our first full year as Co-Editors-in-Chief. As we highlighted in our introductory editorial (Edwards and Schedlitzki, 2023) we see our role as striving to develop the community of the journal in its endeavour to be a key, critical and contemporary voice for leadership studies. To continue this journey, and to help contributors frame and develop their work for submission to the journal, we have invited some of our Associate Editors to share their thoughts on the following questions: 1. What do you look for in a strong article, suitable for submission to Leadership? 2. What do you see as a critical contribution to leadership studies? 3. Can you highlight and/or explore some past articles published in Leadership that exemplify your views? In this editorial we will hear from three of our associate editors - Brigid Carroll, Magnus Larsson and Owain Smolović Jones. As you will see below, they push us towards key thinking around criticality as an edge, encouragement to engage with the complexity of leadership as a phenomenon and promoting ideas around critical companionship. We hope that you enjoy the read!